Position Optimization of Measuring Points in Voltage Non-contact Measurement of AC Overhead Transmission Lines - Dongping Xiao; Yutong Xie; Huaitong Liu; Qichao Ma; Qi Zheng; Zhanlong Zhan, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, an innovative idea is proposed to realize the voltage non-contact measurement of AC overhead transmission lines (OTLs), which is to reversely calculate the voltage characteristic parameters by using the measured AC electric field data under OTLs. The main challenge to realize the goal is the serious illposedness of the inverse problem. The condition number of the observation matrix K is the main index to reflect the ill-posedness of the inverse problem. Because the matrix K is determined by the positions of OTLs and the measuring points of electric field, it is an effective but often overlooked solution to search the optimal positions of measuring points. In this paper, an improved particle swarm optimization algorithm with the adaptive adjustment of inertia weight is developed to search the optimal measuring positions. The presented examples indicate that the selection of optimal positions for the measuring points significantly improves the accuracy and stability of the inverse solution. Meanwhile, the strong searching ability, fast convergence rate, and high stability of the proposed optimal algorithm are demonstrated as well.